Mother Goose's nursery rhymes - Robinson, Charles (New York : Portland House : Distributed by Crown Publishers, Inc., 1987)
An illustrated collection of traditional rhymes.
Previously published as: The Big book of nursery rhymes. 1903.
Includes bibliographical references.
Keywords: Nursery rhymes; Children's poetry; Nursery rhymes